Charge (in)stability and superradiance of Topological Stars - Andrea Cipriani; Carlo Di Benedetto; Giorgio Di Russo; Alfredo Grillo; Giuseppe Sudano (Journal of High Energy Physics)
Abstract We study linear massive scalar charged perturbations of Topological Stars in the fuzzball and in the black hole (Black String) regimes. The objects that naturally couple to the electric 3-form field strength of these solutions are charged strings, wound around the compact direction. We explore the possibility of instabilities of these solutions, in analogy with the charge instability already highlighted for other non-BPS geometries like JMaRT. This issue is addressed by calculating quasi-normal mode frequencies with a variety of techniques: WKB approximation, direct integration, Leaver method and by exploiting the recently discovered correspondence between black hole/fuzzball perturbation theory and quantum Seiberg-Witten curves. All mode frequencies we find have negative imaginary parts, implying an exponential decay in time. This suggests a linear stability of Topological Stars also in this new scenario. In addition, we study the charge superradiance for the Black String. We compute the amplification factor with the numerical integration method and a quantum Seiberg-Witten motivated definition including instantonic corrections.